Clinotron: a Promising Source for THz Regions - Manzhos, S.; Schuenemann, K.; Sosnytskiy, S.V.; Vavriv, D.M. (Радиофизика и радиоастрономия, 2000)
Potentials of the backward-wave oscillator (BWO) with an inclined electron beam (the clinotron) as a source of electromagnetic radiation in THz regions are examined. A self-consistent collective electron-wave interaction theory is developed to study starting conditions and steady state oscillations of clinotron tubes. Optimization of the geometry of pulsed and continuous wave (CW) 1-THz clinotrons is carried out and a possibility of the development of promising tubes for this frequency region is found. Рассмотрены перспективы использования лампы обратной волны с наклонённым электронным пучком (клинотрона) как источника электромагнитного излучения терагерцевого диапазона частот. Для изучения пусковых условий и стационарных колебаний клинотрона разработана самосогласованная теория коллективного взаимодействия электронов с волной. Обнаружена возможность разработки перспективных ламп для терагерцевого диапазона частот и проведена оптимизация геометрии клинотронов импульсного и непрерывного действия с частотой генерации 1 ТГц. Розглянуто перспективи використання лампи зворотної хвилі з нахиленим електронним пучком (клінотрона) як джерела електромагнітного випромінювання терагерцевого діапазону частот. Для вивчення пускових умов та стаціонарних коливань клінотрона розроблено самоузгоджену теорію колективної взаємодії електронів з хвилею. Виявлено можливість розробки перспективних ламп для терагерцевого діапазону частот и проведено оптимізацію геометрії клінотронів імпульсної та безперервної дії з частотою генерації 1 ТГц.